Long term safety, efficacy and clinical outcomes of transobturator tension free tape (inside-out technique) in women with stress urinary incontinence - Penmetsa, Poornima; Guntoory, Indira; Namburi, Ravi K. Raju; M., Jayalaxmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Stress urinary incontinence (SUI) is commonly encountered in Gynaecological practice. The management of stress urinary incontinence underwent a paradigm shift with focus changing from bladder neck suspension to support of mid urethra in the last two decades. The aim of our study is to know the safety, efficacy, subjective and objective outcomes of Transobturator Tension Free Tape (TOT) (in-out technique) in women with Stress urinary incontinence. Methods: This is a prospective study conducted in the departments of Gynaecology and Urology at Maharajah’s Institute of Medical Sciences, Nellimerla, Vizianagaram district, Andhra Pradesh, India. 62 patients were treated with Tension Free Trans-obturator tape with inside-out technique using polypropylene mesh. This study was conducted from June 2012 to May 2014. These women were followed up annually for a period of 3 years af-ter surgery. 3 year subjective and objective outcomes were assessed. Subjective outcome is defined as no loss or leak of urine on physical activity and objective outcome is defined as negative Pad test. Results: The subjective and objective cure rates were 91.93% and 95.16% respectively. Conclusions: Transobturator Tension free Tape is an effective treatment for Stress urinary in-continence in women providing high subjective and objective efficacy upto 3 years after surgery.